EFEKTIVITAS PENAMBAHAN KOTORAN SAPI PADA LIMBAH CAIR TAHU SEBAGAI BAHAN BAKU PEMBUATAN BIOGAS UNTUK PENGEMBANGAN HANDOUT PADA KONSEP BIOTEKNOLOGI KELAS XII SMA - Vinda Hari Yanti; Darmawati '; Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Aims of this research is determine the effectivity of the addition of cow feses in liquid waste out as a raw material for biogas to the development of biotechnology handout on the concept of class XII High School in January 2016 to March 2016. The research was carried out by two stages, experimentation and development handouts. Research experiments conducted using completely randomized design (CRD), which consists of 4 treatments and 3 replications. If there is a real test there will be a further test Duncans Multiple Range Test (DMRT) at 5% level, while the development of handout done using ADDIE models. Parameters used include volume, pH, temperature, and the test flame. The addition of cow manure in liquid waste out effectively in the production of biogas. Treatment B3 (1500 ml liquid waste out + 1200 ml of cow dung) to be most successful in generating biogas, which can produce biogas volume of 8.44 liters and has a blue flame. The results of this study can be used as a handout development by showing category invalid (3.88) on the concept of biotechnology sub class XII High School in the field of biotechnology breeding material.Key Words: Cow Dung, Tofu Liquid Waste, Biogas , Handouts , Biotechnology